ENT 530 Business Plan : Edible Water Bottle / Izham Hajar... [et al.] - Hajar, Izham; Abdul Rahim, Fatin Liyana; Mohd Zaidi, Fatin Liyana; Kudang, Veronicca Babra Monna (2018)
The business of T.M.N.T companies is a business that produces and sell new innovation product which is an edible water bottle and an edible milk bubble. The concept of our product is to make people slowly using less plastic bottle which are dangerous to our earth and also our health. That is why we want to bring this kind of product to food and beverage industries with concept gain profit while conservation the environment. The target markets of our company are children and all people that have different type of age. To inform the existence of our company and services, we have distributed flyers to nearby residential and business premises. In fact, customers can also get information about our company on the website provided. The competitive advantage is as they are already been longer in industries and gain trust from the customer better than us. Next, for the profitability, we are in advantage as there is still no others company that producing the product. Our management team is consisting from very skilful and acknowledge person that will be able to handling the companies very well. There are the general manager, administrative and marketing manager, operation manager and finance manager.